Regulation-Based Safety Redesign of Electric Forklift Charging Panel - Sumardianto, Candra; Jami’in, Mohammad Abu; Nugroho, Priyambodo Nur Ardi; Asmara, I Putu Sindhu (International Journal of Marine Engineering Innovation and Research, 2026)
The increasing use of electric forklifts in industrial environments requires charging power supply systems that are technically reliable and compliant with updated electrical safety regulations. However, empirical studies evaluating the regulatory compliance and safety risks of electric forklift charging panels—particularly under Indonesia’s Minister of Energy and Mineral Resources Regulation No. 1 of 2023—remain limited, indicating a clear research gap. This study aims to assess the compliance level of an existing electric forklift charging power supply panel and to propose a redesigned panel that meets regulatory and safety requirements. An observational assessment was conducted using a structured compliance checklist derived from ESDM Regulation No. 1 of 2023, covering protection systems, grounding, monitoring instruments, labeling, and operational safeguards. Quantitative compliance scoring and risk-based evaluation were applied to identify technical deficiencies and associated electrical hazards. The results show that the existing panel complies with only 58% of mandatory requirements and presents several high-risk conditions, particularly due to inadequate protection devices, lack of electrical monitoring, and insufficient grounding. A redesigned single-line diagram was subsequently developed and evaluated, achieving 100% compliance with mandatory and recommended criteria. The proposed design significantly reduces electrical safety risks, improves system reliability, and ensures full regulatory compliance, providing a practical reference for the development of safe and reliable industrial electric vehicle charging infrastructure.